SIEM: Santiago’ (Chile) Integrated Energy Model: Santiago’ (Chile) Integrated Energy Model - Carbonnel Torralbo , Alexandre; Martin Quijada, Rodrigo (Revista de la Construcción. Journal of Construction, 2018)
This paper presents a framework for the "Santiago Integrated Energy Model" or SIEM. This model establishes an optimized energy balance between the photovoltaic generation potential and the electric consumption curves of a specific Urban Energy District (EUD), designed for the city of Santiago. To validate local data, a methodology has been developed in three stages: the potential prospection and the curves estimation; the data calibration; and the EUD identification. The model has been applied in an hypothetical urban area to develop a consistency test, obtaining adequate results on the balance curves of the model, considering both the potential generation and consumption (according to uses and schedules). The results reflect the relevance of applying this model to a real urban area in Santiago of Chile, to establish optimization correlations for an empirical validation.